Capacity building through efficient use of existing airport infrastructure: Summary report of the Roundtable on Capacity Building through Efficient Use of Existing Airport Infrastructure (9-10 March 2017, Querétaro) - Jagoda Egeland; Paul Smale (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
This paper is based on expert discussions on how airport capacity could be improved to benefit the users of aviation, without building new airport infrastructure. These discussions took place at a Roundtable meeting of 34 experts held in Querétaro, Mexico in March 2017. Roundtable participants took a view that any congested airport represents a market failure with rents accruing either to airlines and/or elsewhere along the value chain. Administrative slot allocation, while it can help achieve particular connectivity outcomes, cannot allocate capacity in a market efficient way. Allocating capacity through market based instruments such as slot auctioning can achieve that goal, but it currently is both technically and politically difficult to implement without creating significant disruption to the network. The distributive impacts of slot allocation regimes and any trade-offs from potential changes to them thus need to be considered by policy makers before deciding on any capacity allocation measures. Participants agreed that a multi-faceted approach is needed to improve welfare of aviation users, which in particular needs to take advantage of technological change in the sector.
Keywords: 330; Flughafenmanagement; Flughafeninfrastruktur; Kapazitätsplanung